Entrepreneurial competence formation of future agricultural economists by means of interactive learning tools - Каландирець, Неля Миколаївна (Pedagogy of Higher and Secondary Education, 2017)
As a result of research the author demonstrates the need to change the system and the style of teaching economic disciplines, offers to use interactive learning methods for future economists in agricultural universities. In the article the following types of interactive learning as business games and case method are considered. Also, the features of their application in studying economic disciplines to form students’ entrepreneurial competence are given. The article highlights the necessity to use interactive learning methods, which means that both individual and group work of students are used in class, their work with documents and various sources of information which helps the student acquire and process much larger amount of information, contributes to his activity and professional skills, gives rise to critical thinking, the ability to give reason for their views and to further self-education. In such a way universities create favorable conditions for modern specialists. It is also noted that the use of these interactive technologies is completely justified in training future economists in agricultural universities, as it ensures mastering professional and entrepreneurial competencies, ability to independently organize their own learning activities, actively and creatively participate in the discussion and analysis of the material studied, and skillfully apply the gained knowledge and skills in practice.